The Effect of Different Disinfecting Agents on Bond Strength of Resin Composites - Ahmed Mohammed Hassan; Ahmed Ali Goda; Kusai Baroudi (International Journal of Dentistry)
Objective. The aim of this study was to evaluate the effect of different disinfectant agents on bond strength of two types of resin composite materials. Methods. A total of 80 sound posterior teeth were used. They were divided into four groups (n=20) according to the dentin surface pretreatment (no treatment, chlorhexidine gluconate 2%, sodium hypochlorite 4%, and EDTA 19%). Each group was divided into two subgroups according to the type of adhesive (prime and bond 2.1 and Adper easy one). Each subgroup was further divided into two subgroups according to the type of resin composite (TPH spectrum and Tetric EvoCeram). Shear bond strength between dentin and resin composite was measured using Universal Testing Machine. Data collected were statistically analyzed by t-test and one-way ANOVA followed by Tukey’s post hoc test. Results. It was found that dentin treated with EDTA recorded the highest shear bond strength values followed by sodium hypochlorite and then chlorhexidine groups while the control group showed the lowest shear bond strength. Conclusions. The surface treatment of dentin before bonding application has a great effect on shear bond strength between resin composite and dentin surface.